Prenatal Testosterone Exposure Induces Hypertension in Adult Females via Androgen Receptor–Dependent Protein Kinase Cδ–Mediated Mechanism. Issue 3 (March 2015) - Blesson, Chellakkan S.; Chinnathambi, Vijayakumar; Hankins, Gary D.; Yallampalli, Chandra; Sathishkumar, Kunju
Abstract : Prenatal exposure to excess testosterone induces hyperandrogenism in adult females and predisposes them to hypertension. We tested whether androgens induce hypertension through transcriptional regulation and signaling of protein kinase C (PKC) in the mesenteric arteries. Pregnant Sprague–Dawley rats were injected with vehicle or testosterone propionate (0.5 mg/kg per day from gestation days 15 to 19, SC) and their 6-month-old adult female offspring were examined. Plasma testosterone levels (0.84±0.04 versus 0.42±0.09 ng/mL) and blood pressures (111.6±1.3 versus 104.5±2.4 mm Hg) were significantly higher in prenatal testosterone–exposed rats compared with controls. This was accompanied with enhanced expression of PKCδ mRNA (1.5-fold) and protein (1.7-fold) in the mesenteric arteries of prenatal testosterone–exposed rats. In addition, mesenteric artery contractile responses to PKC activator, phorbol-12, 13-dibutyrate, was significantly greater in prenatal testosterone–exposed rats. Treatment with androgen receptor antagonist flutamide (10 mg/kg, SC, BID for 10 days) significantly attenuated hypertension, PKCδ expression, and the exaggerated vasoconstriction in prenatal testosterone–exposed rats. In vitro exposure of testosterone to cultured mesenteric artery smooth muscle cells dose dependently upregulated PKCδ expression. Analysis of PKCδ gene revealed a putative androgen responsive element in the promoter upstream to the transcription start site and an enhancer element in intron-1. Chromatin immunoprecipitation assays showed that androgen receptors bind to these elements in response to testosterone stimulation. Furthermore, luciferase reporter assays showed that the enhancer element is highly responsive to androgens and treatment with flutamide reverses reporter activity. Our studies identified a novel androgen-mediated mechanism for the control of PKCδ expression via transcriptional regulation that controls vasoconstriction and blood pressure. Abstract : Supplemental Digital Content is available in the text.